The economic-commercial fights beyond the box. Press, advertising and radio in Argentina in the 20s - Scharagrodsky, Pablo Ariel (Pensar la Publicidad. Revista Internacional de Investigaciones Publicitarias, 2020)
The following work analyzes one of the most famous international boxing fights of the first half of the 20th century: the match for the heavyweight world championship between the Argentinean Luis Ángel Firpo (1894-1960) and the American Jack Dempsey (1895 -1983). The event mobilized a large part of Argentine society. In this multitudinous and unprecedented process of popular mobilization, the written press was a central actor. Taking this into account and taking this ’sporting’ event as a great condenser of meanings, the following work explores, through the critical analysis of discourse and the contributions of social and cultural history, the function that Publicity had, and the senses placed in circulation through advertisements in the Argentine written mass media. Likewise, attention is focused on one of the most original and disseminated products by the advertising of that time: radio. Our hypothesis is that this sporting event produced at the beginning of the decade of the ’20s amplified and consolidated a process that in Argentina was newly setting: the close relationship between sporting events, graphic advertising and radio. After this fight, sport spectacle, advertising and radio triad acquired new political-commercial dimensions in Argentina.